Electronic structure of wurtzite MgO - Jiao, Liuqing (Nanyang Technological University, 2022)
Wurtzite MgO is not a stable structure as a single crystal, but it can be kept in some the special compound system, like ZnMgO. The band structure of wurtzite MgO is already researched in the compound structure with ab initial pseudopotential method based on density function, full-potential linearized muffin-tin orbital method, and firs-principle density functional calculation. Nevertheless, there is no empirical pseudopotential result of the wurtzite MgO band structure, so in this thesis, the band of wurtzite MgO is calculated by this method. The wurtzite MgO band is plotted under different lattice constant ratios. One is the ideal wurtzite MgO in the epitaxy layer on wurtzite ZnO, the other is the non-ideal MgO appearing in ZnMgO alloy when the component of Mg locates in a certain range. For getting a better band structure, it is critical to find out the accurate form factors of the two structures. With the help of a model giving an initial estimation, the suitable form factors are finally found after many times of adjustment. In the end, energy gap and effective mass are extracted from both band plots and these data are compared with those generated by other methods. Otherwise, the data of rock salt MgO——the most stable form of MgO, is also introduced to have a comparison with these structures.